Ovarian pregnancy: an unusual presentation - Hussain, Ayesha Arif; Aziz, Sultana; Sharma, Rina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian pregnancy is a rare type of ectopic pregnancy and usually, it ends with rupture before the end of the first trimester. The clinical picture generally mimics that of ruptured tubal ectopic pregnancy and hemorrhagic ovarian cyst. Transvaginal sonography may be helpful. We report a rare primary ruptured ovarian pregnancy in a 23 years lady.